Characteristics of functional movement screening testing in elite handball players: Indicative data from the 9+ - Rafnsson, E. T.; Myklebust, G.; Bahr, R.; Valdimarsson, Ö.; Frohm, A.; Arnason, A. (Physical Therapy in Sport, 2019)
Objectives: To test 9 + screening batterie's intra-rater reliability, to provide indicative data of elite handball players, and to analyze difference between age, playing positions and level of play. Design: Descriptive study. Setting: Icelandic elite male handball players. Participants: 182 elite male handball players. Main outcome measures: Nine + screening battery. Results: Reliability test: Intra-class correlation for the total score was 0.95. The correlation of each of the test factors varied from 0.63 to 0.91. The mean total score was 22.3 ± 2.9 (95%CI 16.7-28.1), with no difference in total score comparing players age or level of play. Goalkeepers displayed a higher total score than other players (F3,151 = 5.75, p = 0.001). Junior players had a lower score than senior players in tests measuring abdominal strength and core stability; Test 5; ¦2(3, 182) = 41.5, p < 0.0001, Test 6; ¦2(3, 182) = 55.7, p < 0.0001, Test 7; ¦2(3, 182) = 11.8, p < 0.005, but higher scores in tests measuring trunk and shoulder mobility Test 8; ¦2(3, 182) = 18.2, p < 0.0001, Test 9; ¦2(3, 182) = 22.2, p = 0.006. Conclusions: The 9+ intra-rater reliability was acceptable for the total score and individual tests. Age-related differences were provided in many individual tests.